An Analysis of Teachers’ Classroom Management in Teaching English - Ratu Amalia Mudianingrum; Sutrisno Sadji Evenddy; Rosmania Rima (Universitas Mathla'ul Anwar Banten, 2019)
Classroom Management is a multifaceted concept and views about classroom and its styles can be categorized in various ways. This study focused on the classroom itself. Therefore, this study was intended to describe the classroom management and the use of teaching learning strategy at the eight grade students in SMPN 05 Kota Serang. This study was also aimed to give some contributions concerning the Classroom Management Strategy and the students’ participation on the use of the strategy in teaching learning process in the class. This study is qualitative research. The writer had chosen two english teachers who taught the eighth grade students of SMPN 05 Kota Serang in the academic year of 2017/2018 as the subject. The writers describe the process of organizing teaching and learning process in SMPN 05 Kota Serang by applying interview and observation to the teachers. The writers could conclude that T1 applied 72% and T2 applied 70% classroom management strategy in their classroom. They applied the classroom strategies from opening to closing activities, used seating arrangement during the teaching learning process, explained the material well, gave motivation, had positive attitude and built the relationship with students.